Secure and Scalable System by integrating CP-ABE with Proxy - Mr. Vimal Ram, Natasha D’Souza, Dolly D’Souza, Valentine Correia., (International Journal of Scientific Research and Management (IJSRM), 2016)
Data stored in the remote database should be kept in a secure and confidential manner it should not be accessed by any unauthorized user. Some changes are being made to the ABE (Attribute Based Encryption) Algorithm in order to decide the set of users to access the data. The already existing Semi-Trusted authority can be changed to complete trusted authority by only keeping a track of the logs and